Nutrient thresholds to protect water quality, coral reefs, and nearshore fisheries. (November 2022) - Houk, Peter; Castro, Fran; McInnis, Andrew; Rucinski, Michael; Starsinic, Christy; Concepcion, Teddy; Manglona, Storm; Salas, Edwin
Abstract: A ridge-to-reef framework was developed for 26 watersheds around Guam. Dissolved inorganic nitrogen (DIN) data were collected for one year at the base of streams while coral and fish surveys were conducted on adjacent reefs. Two independent analyses revealed a similar 0.10 mg/l DIN threshold beyond which negative impacts to water quality and coral reefs existed. The influence of DIN was next partitioned with respect to a second primary stressor, fishing pressure. While coral diversity was negatively influenced by DIN, the cover of some stress-tolerant corals increased, such as Porites rus, making coral cover alone a poor indicator of watershed pollution. Less intuitive, DIN predicted increased food-fish biomass that was accounted for by generalist herbivores/detritivores, representing homogenized assemblages, while fishing pressure reduced biomass. Our DIN thresholds resonated with a similar study in American Samoa suggesting broader guidance for water quality legislation may be emerging. Graphical abstract: Unlabelled Image Highlights: A ridge-to-reef framework was developed to link watershed characteristics, water quality, fishing pressure, and coral reefs Two independent approaches revealed a similar 0.10 mg/l dissolved inorganic nitrogen (DIN) threshold to prevent impacts DIN reduced coral diversity, increased stress-tolerant corals, and increased biomass of homogenized fish assemblages Fishing pressure reduced all metrics of the coral and fish assemblages Guidance to identify priority stressors and establish DIN thresholds for the broader Pacific was offered